ETIKA PROFESI HAKIM: IMPLEMENTASI DI MAHKAMAH AGUNG DAN DI MAHKAMAH KONSTITUSI - Arisa Sifa; Radhita Armand (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This research aims to discuss the professional ethics of judges, focusing on the application of the judges' code of ethics. Judges have a huge responsibility in carrying out their duties, because the judge's decision can have far-reaching consequences for the lives of judges or other people affected by the reach of their decisions. Thus, the profession of a judge cannot be separated from a set of values that must be owned and upheld by a judge, which is commonly referred to as ethics. The conclusion of this paper is to emphasize that the code of ethics is not only a moral guideline, but also a tool to answer legal issues in society.